Sarcopenia assessments as predictors of overall survival in patients with metastatic renal cell carcinoma - Kümmerl, Luca; Kraulich, Matthias; Lesyuk, Wladimir; Binninger, Adrian; Goebell, Peter; Kahlmeyer, Andreas (Urologic Oncology-Seminars and Original Investigations, 2023)
Background: Sarcopenia represents an important prognostic marker in tumor patients. However, measurement methods and threshold values are not uniformly defined. The aim of this study is therefore to determine the prognostic value of current definitions of sarcopenia in patients with metastatic renal cell carcinoma treated with tyrosine-kinase-inhibitors (TKIs). Methods: In 93 patients with metastatic renal cell carcinoma, sarcopenia was assessed based on manually assisted software measurements of sarcopenia indices based on different muscle areas. Whole muscle area and psoas muscle area at L3 were estimated and adjusted to patient's height in routine CT imaging before the start of first-line TKI therapy. The correlation of different sarcopenia definitions to overall survival was investigated in a univariate analysis as well as in a multivariate analysis. Results: The mean patients’ age at inclusion was 65.8 years (21–86 years). Median survival was 12.3 months (IQR: 5.7–29.8 months), and mean survival was 18.8 months (SD: 17.2 months). As the definitions of sarcopenia differ considerably, 7.6% to 96.7% of the patients were classified as sarcopenic. In univariate analysis, sarcopenia was significantly associated with overall survival. Multivariate analysis, taking into account the Memorial Sloan Kettering Cancer Center risk score, revealed that some sarcopenia-indices are additional and independent prognostic markers. The risk of death was approximately doubled in sarcopenic patients. Conclusions: Sarcopenia is an important prognostic factor in patients with metastatic renal cell carcinoma treated with TKIs. Multivariate analysis demonstrates a doubling of the risk of death in sarcopenic patients. The assessment of sarcopenia can be performed by the analysis of routine staging imaging using indices of the total muscle area or the psoas muscle area.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Overall survival; Prognostic factor; Psoas muscle; Renal cell carcinoma; Sarcopenia; Skeletal muscle; Tyrosine kinase inhibitors